Corporate Governance, Financial Reporting Quality and Firm Performance: A Mediation Analysis - Pham Thi Tuyet, Trinh; Nguyen Van, Nam (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study investigates the relationship between corporate governance (CG) and firm performance (FP), while also examining the mediating role of financial reporting quality (FRQ). The dataset consists of 599 non-financial firms listed on the Vietnamese stock market from 2019 to 2023. The analysis is conducted using panel data models implemented in Stata/MP 17. To assess the mediating effect of FRQ, the study employs the Sobel test to determine the extent to which CG indirectly influences FP through FRQ. The empirical results indicate that CG has a positive impact on FP. Additionally, FRQ is found to partially mediate this relationship, suggesting that CG enhances FP not only directly but also indirectly by improving FRQ. Based on these findings, the research contributes to the literature on CG in emerging markets such as Vietnam, and underscores the critical role of as an effective transmission channel of CG. Managerial implications, limitations, and future research are also discussed.